Dietary inclusion of blood hydrolysates affects muscle growth in European seabass (Dicentrarchus labrax) - Velasco, Cristina; Resende, Daniela; Oliveira, Beatriz; Canada, Paula; Pereira, Miguel; Pereira, Carlos; Pintado, Manuela; Valente, Luisa M. P. (Frontiers in Marine Science, 2023)
Dietary supplementation with hydrolysates has been suggested to influence muscle protein synthesis and fish growth. This study assessed the impact of including 3% swine blood hydrolysates (BH) in a plant-based diet on muscle cellularity and the expression of molecular markers related to muscle fibre proliferation and hypertrophic growth of European seabass. Three BH fractions were obtained by two different processes, autohydrolysis (AH-H) and enzymatic hydrolysis followed by micro- (RMF-H) and nanofiltration (RNF-H). Each BH was added to a commercial-based diet, where 50% of fishmeal was replaced by vegetable proteins (negative control, NC). A fishmeal-based diet was used as positive control, PC. The diets were fed to juveniles (12 g) during 74 days. The RMF group showed down-regulation of myod1 and fgf4, essential to myoblast proliferation and differentiation, and upregulation of mafbx, responsible for protein breakdown, resulting in impairment of muscle hyperplasic growth and the lowest muscle fibres number. However, compensatory growth mechanisms were observed through capn1 downregulation and mymk upregulation, suggesting decreased muscle proteolysis and increased myoblast fusion. Despite this, the compensatory mechanisms were insufficient as RMF group had the worst growth. RNF group had a final weight similar to the NC, but downregulation of fgf4, fgf6 and capn1 may compromise growth potential at long term. The expression of these genes in the AH group was similar to that in the FM-based diet. Despite not having demonstrated growth promotion ability, BH affect muscle growth and cellularity factors, prompting further research on commercial-sized fish to reveal their impact on important commercial traits.